Energy benefits of cement-based plaster containing hybrid phase-change material - Kheradmand, Mohammad (2018)
This paper reports an experimental study regarding the energy-saving potential of an innovative concept of thermal energy storage, which consists of embedding three types of phase-change material (PCM) into a cement-based mortar for plastering the inside walls of buildings. The so-called ?hybrid phase-change material mortars? can enhance energy saving when compared with single PCM mortars. They increase the range of melting temperatures and enthalpies, thus providing a more staged and progressive energy exchange. The experimental programme comprised two hollow boxes, one internally rendered with hybrid mortar and the other with a reference mortar without PCM. They were then externally subjected to realistic daily winter temperature profiles. The prototypes were internally equipped with a heater programmed to keep the inside of the boxes at a comfortable room temperature. The energy consumption in the box rendered with hybrid mortar was nearly 20% less than that of the box rendered with standard mortar. The potential cost savings of hybrid PCM mortars for residential buildings are also discussed.